Spontaneous Intracranial Hemorrhage in a 34-Year-Old Male Patient Related to Hypertensive Emergency - Nurmalasari, Mifta; Widodo, Djoko (AKSONA, 2024)
Highlight: Unhealthy lifestyles are believed to be cause of hypertension at a young age. Untreated hypertension increases cardiovascular disease morbidity and mortality. The incidence of intracranial hemorrhage associated with hypertension is approximately 60%. It commonly occurs in the deep brain structure, which is considered to have a poor clinical outcome.   ABSTRACT Introduction: The incidence of hypertension is currently moving toward younger ages. It’s thought that an unhealthy lifestyle serves as a trigger. Hypertension can increase morbidity and mortality related to cardiovascular disease, even at a young age. This case report is intended to report the incidence of spontaneous intracranial hemorrhage in a 34-year-old male patient during a hypertensive emergency. Case: A 34-year-old male patient was rushed to the emergency unit at midnight due to a sudden decrease in consciousness. Headaches and seizures occurred before admission. The patient denied having any history of head trauma. The patient’s habits included excessive caffeine consumption, frequent late-night sleeping, and extensive smoking. At the time of admission, the patient’s vital signs indicated a poor clinical condition: GCS E1V1M1, BP 212/118 mm/Hg, deep irregular rapid breathing, sometimes followed by periodic apnea, RR 28 breath/minute, HR 111 beat/minute, SpO2 50%, T 36.8°C, which gradually developed hyperthermia. Both eyes had constricted and fixed pupils; the light reflexes were negative. A neurological examination revealed the body’s left lateralization. The head CT scan without contrast indicated hemorrhage in the right intracerebral, midbrain, pons, intraventricular, and subarachnoid areas, with estimated total volume of about 31 ml. Conservative treatment was chosen due to the bleeding location in the deep brain structure of GCS 3, which was considered to have a poor outcome. Conclusion: Hypertension in the younger age group is commonly associated with unhealthy lifestyles, which increase morbidity and mortality related to cardiovascular disease.